A Study of Flood Causal Priority in Arui Watershed, Manokwari Regency, Indonesia - Mahmud, Mahmud; Kusumandari, Ambar; Sudarmadji, Sudarmadji; Supriyatno, Nunuk (Jurnal Manajemen Hutan Tropika, 2018)
Papua is the final fortress of forests in Indonesia. However, floods recently occurred in Jayapura, Paniai, and Manokwari. If causal factors are not identified and early anticipated, the flood will become an annual disaster with more severe impacts. This study aims to identify main factors causing floods using scoring analysis. Data collected include: rainfall, river gradient, water discharge, drainage density, watershed shape, slope and land use. The research results show that the main factor of floods are average daily rainfall in wet month by 86.53 mm day-1 (rather high) with a score of 28, land use dominated by forest and plantation (rather low and medium) with a score of 21, watershed slope dominated by 1-